Conducting the energy analysis as a component of the energy management system of higher education institutions - Nosachenko, M. P.; Kovalenko, S. M.; Zborovska, T. V. (Social Pharmacy in Health Care, 2024)
Aim. To conduct the energy analysis of a higher education institution and form proposals for improving the energy management system in the context of using electricity and heat energy on the basis of a higher education institution (HEI). Materials and methods. Informational, retrospective, based on the study of scientific literature, materials of Internet resources and own conclusions were used. Results. One of the important elements of the organization’s energy management system is the collection of energy information and conducting the energy analysis. The collection of energy information and energy analysis of HEI, which forms the basis of the implemented energy management system, have been carried out. All sources of HEI energy to form the system of energy consumption of HEI have been determined and quantified. Data on costs and consumption of electricity and heat energy have been analyzed; it has allowed determining positive trends in energy consumption in HEI. Low-cost and medium-cost measures to preserve fuel and energy resources of HEI have been proposed within the framework of the implemented energy management system. Conclusions. The collection of energy information and energy analysis of HEI, which forms the basis of the implemented energy management system, have been carried out. All sources of HEI energy to form the system of energy consumption of HEI have been determined and quantified. A number of effective measures have been proposed to improve the energy management system of HEI in the context of using electricity and heat energy.